DIAGNOSIS OF DETERMINATION OF THE LEVEL OF PROFESSIONAL COMPETENCE OF TEACHERS IN THE PROCESS OF PROFESSIONALIZATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is awarded to the retraining and advanced training of teachers of teachers of students.